100 megahertz-rate ultrahigh-speed digital holography instrument. (1st August 2022) - Mansoor, M.M.; George, J.
Abstract: This work presents the development of an ultrahigh-speed digital holography instrument that can perform volumetric measurements at a rate of up to 100 million frames per second. The system is based on an Ultra 8 camera that uses a single custom-built image intensifier with a segmented photocathode that can gate eight different imaging regions down to 10 ns. An in-line interferometric scheme is used to capture the deformation of a water drop as it is photoablated from irradiation by a 1064 nm wavelength pulsed laser beam. After a digital holographic video is captured, wavefront reconstruction is used to focus on discrete depth planes enabling the user to observe different 3-dimensional features of the drop as the field-of-view is scanned plane-by-plane. The reconstructions are detwinned and corrected for parallax and alignment error before a final image at any given depth is produced. We provide one-to-one comparisons between conventional focused imaging and digital holography to demonstrate the 3-dimensional visualization capabilities of the instrument with particular regard to dynamic events occurring at nanosecond time intervals for future applications to hypersonic flows and other short and ultrashort duration events.